EFFECT OF EPIDURAL AND GENERAL ANESTHESIA ON PERIOPERATIVE NEUTROPHIL LYMPHOCYTE RATIO CHANGES IN MASTECTOMY PATIENTS - Damayanti, Fina; Harahap, Muhammad Wirawan; Karim, Abdul Mubdi Ardiansar Arifuddin; Sommeng, Faisal; Swarga, Tirta (International Journal of Health Science & Medical Research, 2026)
Mastectomy induces a systemic inflammatory response that may be influenced by the anesthetic technique, as reflected by changes in the neutrophil–lymphocyte ratio (NLR). Unlike previous studies that assessed mixed breast surgeries, broadly evaluated regional anesthesia, or focused on combined general–epidural techniques and cytokine markers, this study uniquely compares perioperative pre–post changes in NLR (ΔNLR) between epidural anesthesia alone and general anesthesia alone in mastectomy patients using a routinely available biomarker. This quantitative experimental study was conducted at Ibnu Sina YW-UMI Hospital, Makassar, from August 2025, involving 30 mastectomy patients recruited consecutively and allocated into two independent groups (15 epidural, 15 general anesthesia). Venous blood samples were collected preoperatively and 24 hours postoperatively to calculate NLR, with ΔNLR as the primary outcome. Within-group analysis using the Wilcoxon test showed significant postoperative increases in NLR in both the epidural group (5.13 ± 5.42 to 7.65 ± 5.99; p0.001) and the general anesthesia group (4.12 ± 4.59 to 14.72 ± 8.43; p0.001). Between-group comparison using the Mann–Whitney test demonstrated that ΔNLR was significantly higher in the general anesthesia group (10.60 ± 7.23) than in the epidural group (2.52 ± 2.36; p0.001). These findings indicate that epidural anesthesia is associated with a smaller postoperative increase in NLR, suggesting better attenuation of the systemic inflammatory response after mastectomy. Further randomized studies with larger samples, additional inflammatory biomarkers, and clinical outcomes are recommended to enhance evidence strength and generalisability.